Redescription of Argyresthia mirabiella Toll, 1947 (Lepidoptera: Argyresthiidae) - Baraniak, Edward; Walczak, Urszula (Zootaxa, 2015)
Moths of the family Argyresthiidae are widely distributed globally, as they include a few cosmopolitan species (Dugdale et al. 1999). So far the family has not been the subject of any monograph, and the systematic position of many species is unclear (Agassiz 1996). This applies also to Argyresthia mirabiella (Toll, 1947). Its type specimen with the microscopic slide of the female genitalia is deposited in the collection of S. Toll, at the Institute of Systematics and Animal Evolution, Polish Academy of Sciences (Krakow, Poland). Toll’s (1947) description of this species is limited to a few lines of text. The female genitalia are described in a few sentences concerning the antrum, ductus bursae, and signum. The drawing is schematic and greatly simplified. That brief description of A. mirabiella does not allow its proper identification. Here we provide a more detailed re-description and illustrations based on a re-examination of the type.